Gold@Mesoporous Polydopamine Nanocomposite Hydrogel Loaded with Estrogen for the Treatment of Skin Photoaging - Li D; Wang Y; Zhao W; Li L; Zhang P (International Journal of Nanomedicine)
Dashuai Li,1 Yonghua Wang,2 Wanyi Zhao,3 Liqun Li,3 Pan Zhang3 1Department of Stomatology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China; 2Department of Ophthalmology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of China; 3Department of Plastic Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People’s Republic of ChinaCorrespondence: Pan Zhang, Email 15257752896@163.comIntroduction: Topical application of 17β-estradiol (E2) has been shown to improve various hallmark features of skin aging, including enhancing skin elasticity and hydration, reducing wrinkles, and promoting collagen synthesis. However, the role of estrogen in UVB-induced photoaging of the skin remains unclear. Furthermore, E2’s clinical application is limited by issues such as bioavailability and potential adverse effects. Therefore, this study aims to explore the role of E2 in UVB-induced skin photoaging and to prepare a gold (Au)@mesoporous polydopamine (mPDA)-hyaluronic acid (HA)/carboxymethyl chitosan (CMCS) nanoparticle composite hydrogel (Au/E2@mPDA-HCG) for the treatment of skin photoaging.Methods: This study successfully fabricated mPDA with a well-defined mesoporous structure and incorporated Au NPs into the mesopores of mPDA using an in situ growth method, thereby constructing Au@mPDA NPs loaded with E2. Subsequently, the Au/E2@mPDA NPs were embedded into a HA/CMCS hydrogel to develop the Au/E2@mPDA-HCG nanoparticle composite hydrogel. The composite hydrogel was characterized through in vitro and in vivo experiments, and its efficacy in improving skin photoaging was evaluated.Results: This study revealed that estrogen deficiency significantly exacerbates UVB-induced skin photoaging, likely through mechanisms closely associated with increased oxidative stress and reduced collagen production. Moreover, the Au/E2@mPDA-HCG nanoparticle composite hydrogel demonstrated favorable morphological characteristics and biocompatibility. In vitro and in vivo experimental results indicated that this composite hydrogel effectively enhanced the therapeutic efficacy of E2 in treating skin photoaging, as evidenced by its significant mitigation of oxidative stress and inflammatory responses, along with the promotion of collagen synthesis.Conclusion: In conclusion, this study suggests that the combination of E2 with Au@mPDA@HCG nanocomposite hydrogel offers a promising therapeutic strategy for UVB-induced skin photoaging.Keywords: estrogen, skin photoaging, Au nanoparticle, mesoporous polydopamine, hyaluronic acid /carboxymethyl chitosan hydrogel